PENGARUH PEMANFAATAN PERPUSTAKAAN SEKOLAH TERHADAP HASIL BELAJAR SOSIOLOGI SISWA KELAS X SMAN 5 PONTIANAK - Oetami, Putri; Zakso, Amrazi; ., Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis reseach entitled “The Influence of School Libraries Utilization to The Study Result of Sociology Subjects Class X Students in SMA Negeri 5 Pontianak". The general problem is "How is the influence of school librarys utilization to the study result of sociology subjects class X students in SMA Negeri 5 Pontianak?" The method used is descriptive statistics method with a sample of 182 respondence. The techniques of data collection used are indirect communication techniques and documentation techniques. The tools of data collection used are questionnaires and data recap value of sociology subjects re-examinations at class X students in SMA Negeri 5 Pontianak. The technique of data analysis used calculation of product moment and to knowing the influence of independent variable to dependent variable is used "t" test . The results showed that there was a significant impacts in utilization of school library on the study result of sociology subjects as much as 72.7%. Based on these results, the teachers of sociology subject are advised to often encourage the students to more often utilize the collection of sociology books in the school library. And for the school are recommended to increase more facilities of the school library to be better again. Keyword: The Influence of School Library Utilization, The Study Result of Sociologi Subjects